2010
DOI: 10.1097/mlr.0b013e3181f38006
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mortality and Medical Spending in Patients Hospitalized for Community-Acquired Pneumonia

Abstract: Background-Community-acquired pneumonia (CAP) is the most common infectious cause of death in the United States. To understand the impact of efforts to improve quality and efficiency of care in CAP, we examined trends in mortality and costs among hospitalized CAP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
3
27
2
1
Order By: Relevance
“…Although similar findings have been reported in other U.S. studies of hospitalization for CAP, [20][21][22] it is important to note that the composition of hospitals represented in the study database may have changed over time and that some of the observed changes in patient clinical and demographic characteristics may be reflective of a changing collection of sampled hospitals. The percentage of patients who were white, for example, decreased from 82% in 2000 to 73% in 2009, whereas the percentage of patients with various comorbidities increased, including asthma (from 6% to 14%), other respiratory diseases (from 31% to 43%), renal failure (from 4% to 22%), diabetes (from 15% to 24%), coronary heart disease (from 20% to 26%) and alcohol/drug abuse (from 8% to 16%) (all P , 0.01).…”
Section: Resultssupporting
confidence: 81%
“…Although similar findings have been reported in other U.S. studies of hospitalization for CAP, [20][21][22] it is important to note that the composition of hospitals represented in the study database may have changed over time and that some of the observed changes in patient clinical and demographic characteristics may be reflective of a changing collection of sampled hospitals. The percentage of patients who were white, for example, decreased from 82% in 2000 to 73% in 2009, whereas the percentage of patients with various comorbidities increased, including asthma (from 6% to 14%), other respiratory diseases (from 31% to 43%), renal failure (from 4% to 22%), diabetes (from 15% to 24%), coronary heart disease (from 20% to 26%) and alcohol/drug abuse (from 8% to 16%) (all P , 0.01).…”
Section: Resultssupporting
confidence: 81%
“…A similar downward trend in mortality due to CAP has been reported in two previous studies8 9 using US national databases, where mortality due to CAP fell from 8.9% in 1993 to 4.1% in 2005 (p<0.001) in hospitalised patients8 and from 13.5% in 1987 to 9.7% in 2005 in a population of elderly inpatients and outpatients with CAP 9…”
supporting
confidence: 79%
“…Additionally, several county governments have provided free influenza vaccines to all the county's elderly population and pneumococcal vaccinations to all the county's older elderly (age 75 and older) since 2000 33,34 . Other studies have also shown declining mortality rates among patients with pneumonia over the past 10-20 years 17,35 .…”
Section: Discussionmentioning
confidence: 98%